Nutritional deficiencies and children's behavior and mental development - Simeon, Donald T.; Grantham-McGregor, Sally M. (My University, 1990)
The review considers the effects of nutritional deficiencies on behaviour and mental development in children. It briefly discusses iodine and iron deficiencies, and short-term food deprivation before focusing on protein-energy malnutrition (PEM). It concludes that there is an increasing amount of evidence that these nutritional deficiencies detrimentally affect children’s concurrent mental functions. In the case on iodine and probably severe PEM in poor environments, long-term effects have also been demonstrated. It is likely that iron deficiency and mild to moderate under-nutrition, if allowed to persist for long periods, may lead to developmental lags that are difficult to reverse. The long-term effects of recurrent short-term food deprivation are unknown.
Keywords: Malnutrition